An Exploration of Literary Genres Through the Eyes of Pre-Service English Teachers - Gamze Erdem Cosgun (Educational Process: International Journal)
Background/purpose – As teachers of the future, pre-service English teachers’ perceptions towards literary genres were crucial as their thoughts and experiences during their teacher training program would be decisive on their use of literature in their future teaching professions. Therefore, the objective of this qualitative explanatory case study is to explore how pre-service English teachers feel about studying various genres of literature in their English literature courses and the challenges they face, and to present suggestions for using literary extracts more efficiently in ELT classrooms.